2011
DOI: 10.1177/0032885511415223
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Policies and Practices for Drug-Involved Offenders

Abstract: Research on effective rehabilitation of drug-involved offenders has advanced considerably in recent years. Yet policies and practices remain rooted in sentiments from decades past when authorities did not know how to supervise drug offenders closely, apply effective behavioral consequences, or treat the disease of addiction. This article reviews evidence-based practices in sentencing, supervision, treatment, and reentry for drug-involved offenders, drawing on painful lessons from past failed policies. Recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The differential intervention framework, advanced by the RNR model, has recently resulted in several different conceptual models that outline some priorities for assigning offenders to specific programming. Marlowe () offered a substance use disorder diagnosis (dependence or abuse) by criminal risk (high‐moderate and low) placement matching framework. In this framework, high‐ and moderate‐risk offenders with substance dependence are targets for highly structured drug treatment courts, status hearings, restrictive consequences, and positive reinforcements.…”
Section: Study Backgroundmentioning
confidence: 99%
“…The differential intervention framework, advanced by the RNR model, has recently resulted in several different conceptual models that outline some priorities for assigning offenders to specific programming. Marlowe () offered a substance use disorder diagnosis (dependence or abuse) by criminal risk (high‐moderate and low) placement matching framework. In this framework, high‐ and moderate‐risk offenders with substance dependence are targets for highly structured drug treatment courts, status hearings, restrictive consequences, and positive reinforcements.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Further, SUD treatment programs within correctional institutions are often unwilling to adopt the use of medications to treat opioid use disorders (Kubiak et al, 2009;Rich et al, 2005;Smith-Rohrberg et al, 2004). In particular, the use of agonist SUD medications is limited by its being viewed in the criminal justice system as drug substitution (Friedmann et al, 2012;Marlowe, 2011;McMillan & Lapham, 2005;Walters et al, 2007). Other studies using samples of prisons, jails, or community corrections agencies indicate that MAT is rarely used (Friedmann et al, 2012;Matusow et al, 2013;Taxman et al, 2007).…”
Section: Barriers To the Adoption Of Injectable Naltrexonementioning
confidence: 99%
“…This finding was not unexpected, given the work of Kubiak and colleagues (2009) who surveyed state Department of Corrections leaders and found that medications were generally not a highly prioritized treatment service for these purchasers of treatment services. Historically, the criminal justice system has been slow to view MAT as an acceptable part of the treatment process (Chandler et al, 2009; Marlowe, 2011), and few correctional institutions have actively attempted to refer opioid-dependent offenders to MAT in the community (Rich et al, 2005; Nunn et al, 2009). Despite the consistency between our findings and these prior studies, more data are needed to develop an in-depth understanding of the reasons behind the limited adoption and implementation of medications for individuals involved with the criminal justice system.…”
Section: Discussionmentioning
confidence: 99%